Malignancies after mitoxantrone for multiple sclerosis: A retrospective cohort study. (7th June 2016) - Buttmann, Mathias; Seuffert, Linda; Mäder, Uwe; Toyka, Klaus V.
Abstract : Objective: To assess the therapy-related risk of malignancies in mitoxantrone-treated patients with multiple sclerosis. Methods: This retrospective observational cohort study included all mitoxantrone-treated patients with multiple sclerosis seen at our department between 1994 and 2007. We collected follow-up information on medically confirmed malignancies, life status, and cause of death, as of 2010. Malignancy rates were compared to the German national cancer registry matched for sex, age, and year of occurrence. Results: Follow-up was completed in 676 of 677 identified patients. Median follow-up time was 8.7 years (interquartile range 6.8–11.2), corresponding to 6, 220 person-years. Median cumulative mitoxantrone dose was 79.0 mg/m 2 (interquartile range 50.8–102.4). Thirty-seven patients (5.5%) were diagnosed with a malignancy after mitoxantrone initiation, revealing a standardized incidence ratio of 1.50 (95% confidence interval [CI] 1.05–2.08). Entities included breast cancer (n = 9), colorectal cancer (n = 7), acute myeloid leukemia (n = 4, 0.6%), and others (each entity n = 1 or 2). The standardized incidence ratio of colorectal cancer was 2.98 (95% CI 1.20–6.14) and of acute myeloid leukemia 10.44 (95% CI 3.39–24.36). It was not increased for other entities including breast cancer. Multivariate Cox regression identified higher age at treatment initiation but neither cumulative mitoxantrone dose (>75 vs ⩽75 mg/m 2 ) nor treatment with other immunosuppressive drugs or sex as a risk factor. Fifty-five patients had died, among them 12 of a malignancy and 43 reportedly of other causes. Conclusions: While the overall incidence of malignancies was only mildly increased, the risk of leukemia and colorectal cancer was heightened. If confirmed, posttherapy colonoscopy could become advisable.